Science in Latin America : A History - Vessuri, Hebe M. C.; Saldaña, Juan José; Quevedo, Emilio; Madrigal, Bernabé; López-Ocón, Leoncio; Lozoya, Xavier; Lafuente, Antonio; Gutiérrez, Francisco; Cueto, Marcos; Cabral, Regis; Arboleda, Luis Carlos; Arango, Diana Soto (Book collections on Project MUSE., 2021)
Science in Latin America has roots that reach back to the information gathering and recording practices of the Maya, Aztec, and Inca civilizations. Spanish and Portuguese conquerors and colonists introduced European scientific practices to the continent, where they hybridized with local traditions to form the beginnings of a truly Latin American science. As countries achieved their independence in the nineteenth century, they turned to science as a vehicle for modernizing education and forwarding "progress." In the twentieth century, science and technology became as omnipresent in Latin America as in the United States and Europe. Yet despite a history that stretches across five centuries, science in Latin America has traditionally been viewed as derivative of and peripheral to Euro-American science. To correct that mistaken view, this book provides the first comprehensive overview of the history of science in Latin America from the sixteenth century to the present. Eleven leading Latin American historians assess the part that science played in Latin American society during the colonial, independence, national, and modern eras, investigating science's role in such areas as natural history, medicine and public health, the eighteenth-century Enlightenment, politics and nation-building, educational reform, and contemporary academic research. The comparative approach of the essays creates a continent-spanning picture of Latin American science that clearly establishes its autonomous history and its right to be studied within a Latin American context.